Karakteristik Smellscape di Kawasan Stasiun Tugu Yogyakarta - Nurul Fadhillah; Syam Rachma Marcillia (Universitas Muhammadiyah Palembang, 2024)
The area around stations is often the focal point of studies on smellscape, a complex phenomenon that involves human perception and experience of various scents in their environment. In this study, analyze the characteristics of the smellscape in the Tugu Station area of Yogyakarta. This research aims to explore the characteristics of the smellscape in Yogyakarta Tugu Station Area. This research method uses smellwalk and questionnaire. The results showed from the data analysis, that the most dominant types of odors include food odors, carbon emissions, and synthetic odors. Factors such as commercial activities, vehicle traffic, chemical use, population density, and environmental conditions are the main determinants in the formation of the smellscape at this location. Our findings provide a better understanding of the complexity of the urban smellscape in Yogyakarta's Stasiun Tugu area and provide a foundation for the development of more effective environmental management strategies.